Extended Classification of Complement Clause Possibilities for Thinking Verbs - Nurrahmi, Nurrahmi; Machmoed, Hamzah A.; Saleh, Noer Jihad (Hasanuddin University, 2022)
This paper investigates further elaboration of syntactic properties of Thinking verb. All data required for this study are taken in Corpus of Contemporary American English. This paper aims to analyse the complement clause possibilities in Thinking verbs and the sentence structure based on the data found in COCA. The research is conducted through qualitative procedures by categorizing a certain construction of the sentences and interpreting certain context related to the data. The feature of complement clause in Thinking verb has special properties; the ‘That’ is constituted in all verb types. ‘WH’ and ‘ING’ exist in Thinking verbs (except Conclude), Solve and Believe subtypes. ‘Judgment TO’ is found in Think, Assume, Remember, Know (except teach), Conclude and Believe (except Doubt) subtypes. ‘Modal (FOR) TO’ is generally formed in Think subtype (except Consider), Assume subtype (except Suppose), Ponder subtype, Remember subtype, Know subtype (except Sense), Conclude subtype (except Infer), Solve and Believe subtypes. The extended classification of Complement Clause possibilities in Thinking verbs resulted the expand of sentence classification as constituent part, Complement clause possibilities are enriched into some verb types and the data are mostly found in complex sentence.